On the theory of current states in superconducting junctions of SNINS type - Sakhnyuk, V.E.; Svidzynskyj, A.V. (Condensed Matter Physics, 2006)
The behavior of the order parameter close to the NS interface in an SNINS junction is considered. To this
end, a linear integral equation, which is valid near the superconductor-normal metal interface, is obtained
and researched. The Ginzburg-Landau equation is solved taking into account the effect of the current on
the space behaviour of the order parameter. Applying the method of quasiorthogonality to asymptotics, the
boundary condition for the Ginzburg-Landau equation is obtained. The calculation of the current states, which
can exist in an SNINS junction is carried out. We assume the normal layer thickness to be arbitrary and the
temperature to be close to critical.